Infinite order differential equations in the space of entire functions of minimal type with respect to a proximate order - Jin, Xiaoran (North-Western European Journal of Mathematics, 2021)
In this paper, we consider the space of entire functions of minimal type growth for a proximate order. We study the surjectivity of corresponding in- finite order differential equations in the cases of regular singular type and of Korobeı̆nik type.